PHYSICAL QUALITY OF BALI BEEF MARINED WITH SOLUTION OF PINEAPPLE (Ananas comosus) - C., Clarisa; Sriyani, N.L.P.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2023)
The purpose of this study was to determine the physical quality of Bali beef marinated with solution of pineapple ( Ananas comosus ). The design used in this study was a completely randomized design (CRD) with four treatments and four replications. The treatments given were marinating with distilled water as a control, marinating with solution of pineapple for 15 minutes, 30 minutes, and 45 minutes. The variables observed in this study were pH, color, water holding capacity, cooking loss, and raw shrinkage. The results of this study showed that the physical quality of bali beef marinated with solution of pineapple ( Ananas comosus ) had a significant effect (P<0,05) on pH, and color, but had no significant effect (P>0,05) on water holding capacity, raw and cooking losses. From the results of this study, it can be concluded that the proper time to marinate Bali beef with solution of pineapple ( Ananas comosus ) is 15 minutes. Keywords: bali beef, physical quality, marinade, solution of pineapple